Cross-nanofin-based waveplate pixels for broadband hybrid polarization coding in near-field - Du Shuo; Liu Zhe; Sun Chi; Zhu Wei; Geng Guangzhou; Ye Haitao; Li Junjie; Gu Changzhi (Nanophotonics, 2021)
As an inherent characteristic of light, polarization plays important roles in information storage, display and even encryption. Metasurfaces, composed of specifically designed subwavelength units in a two-dimensional plane, offer a great convenience for polarization manipulation, yet improving their integrability and broadband fidelity remain significant challenges. Here, based on the combination of various subwavelength cross-nanofins (CNs), a new type of metasurface for multichannel hybrid polarization distribution in near-field is proposed. Sub-wavelength CN units with various waveplate (WP) functionalities, such as frequency-division multiplexing WP, half-WP and quarter-WP are implemented with high efficiency in broadband. High-resolution grayscale image encryption, multi-image storage and rapid polarization detection are demonstrated by encoding the WP pixels into single, double and four channels, respectively. All these applications possess good fidelity in an ultrabroad wavelength band from 1.2 to 1.9 µm, and the high degree of integrability, easy fabrication and multifunction make the CN-shaped WP pixels a promising candidate in optical device miniaturization, quantum applications and imaging technologies.